THE FACTORS AND REASON BEINGS WHY THE PEOPLE DECIDED TO STAY IN THE FLOOD HAZARD AREA KELURAHAN LAMBUNG BUKIT KECAMATAN PAUH PADANG - Ardimansyah, Poni - (STKIP PGRI Sumbar, 2014)
This research is aimed to get the data and informations about the factors and reason beingswhy the people decided to stay in the flood hazard area, Kelurahan Lambung Bukit KecamatanPauh Padang. These factors can be seen from the perspective of their economy, their educationand their indigenous lands.This research is a descriptive research. The population here is the 137 families affected bythe flood. The respondent samples were taken in proportional random sampling in 50% so thereare 69 samples. The data is proce ared with descriptive statistic with precentage formula.From the research it is found that: (1) the factors why people decided to stay in the floodhazard area from the economic perspective are: their ability to afford to get new places, theiroccupation in the agriculture, and their side jobs. (2) the facrors why the people decided to stay inthe flood hazard area from the education perspective because the locations of public schoolnearby like the elementary school and junior high school. (3) the factors why the people decided tostay in the flood hazard area because it is the indigenous lands they inherited from their ancestorswhich is used for both their life assurance and farming.